2022
DOI: 10.1002/jlb.3mr0822-761rr
|View full text |Cite
|
Sign up to set email alerts
|

The role of γδ T17 cells in cardiovascular disease

Abstract: Due to the ability of γδ T cells to bridge adaptive and innate immunity, γδ T cells can respond to a variety of molecular cues and acquire the ability to induce a variety of cytokines such as IL-17 family, IFN-γ, IL-4, and IL-10. IL-17 + γδ T cells (γδ T17 cells) populations have recently received considerable interest as they are the major early source of IL-17A in many immune response models. However, the exact mechanism of γδ T17 cells is still poorly understood, especially in the context of cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 233 publications
(421 reference statements)
0
1
0
Order By: Relevance
“…Surface markers such as CD27 and CCR6 can be used to define these two subsets ( Haas et al, 2009 ; Ribot et al, 2009 ). In humans, γδ T cells can be distinguished by the δ chain, including Vδ1, Vδ2, Vδ3, and Vδ5 ( Ling et al, 2022 ). While previous studies have reported methods for in vitro expansion of human γδ T cells ( Ness-Schwickerath et al, 2010 ; Caccamo et al, 2011 ; Hur et al, 2023 ), the majority of peripheral blood γδ T cells in humans are Vδ2 + subsets that mainly produce IFN-γ.…”
Section: Introductionmentioning
confidence: 99%
“…Surface markers such as CD27 and CCR6 can be used to define these two subsets ( Haas et al, 2009 ; Ribot et al, 2009 ). In humans, γδ T cells can be distinguished by the δ chain, including Vδ1, Vδ2, Vδ3, and Vδ5 ( Ling et al, 2022 ). While previous studies have reported methods for in vitro expansion of human γδ T cells ( Ness-Schwickerath et al, 2010 ; Caccamo et al, 2011 ; Hur et al, 2023 ), the majority of peripheral blood γδ T cells in humans are Vδ2 + subsets that mainly produce IFN-γ.…”
Section: Introductionmentioning
confidence: 99%